Brands and Urban Life: Specialty Coffee, Consumers, and the Co-creation of Urban Café Sociality. (February 2014) - Bookman, Sonia
While brands are recognized as salient features of the cultural and economic life of cities, the specificity of brands and their impact on urban life has been insufficiently analyzed. Drawing on recent branding theory, and taking the case of specialty coffee brands, this article considers the dynamic process through which these brands frame and co-generate a "third place" experience as part of the functioning of the brand interface and creation of brand value. It highlights the role of consumers in this process, tracing the ways in which they routinely conduct third place social interactions, construct hospitable space, and establish patterns of social relation on the platform of the brand. It is argued that the emergence of an "urban café sociality" characterized by specific forms of togetherness and (limited) modes of belonging is a productive effect of the interactive interplay between brands and consumers in everyday urban life.